2010
DOI: 10.1111/j.1399-0004.2009.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analyses of premature ovarian failure using karyotyping and interphase fluorescence in situ hybridization (FISH) in a group of 1000 patients

Abstract: To evaluate the implication of chromosome abnormalities in the etiology of premature ovarian failure (POF), 1000 patients with POF recruited at the Department of Cytogenetics of Farhat Hached Hospital (Sousse, Tunisia) between January 1996 and December 2008. Chromosome analyses were performed by using karyotyping and interphase fluorescent in situ hybridisation (FISH) using a centromeric probe of the chromosome X to look for low-level mosaicism of X-chromosome monosomy. Hundred and eight chromosomal abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 11 publications
4
63
2
7
Order By: Relevance
“…There is no clear evidence to indicate the effect of an X trisomy on human fertility, as the strong relationship between an X trisomy and POI is clearly revealed [22]. In fact, our data may support that women with X chromosome mosaicism may experience premature menopause [13,20]. The prevalence of 47,XXX in cases with mosaic pattern was 10.7 %, which is higher than the prevalence reported by Goswami et al [5] (3.8%) and Jiao et al [12] (1.5%), respectively.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…There is no clear evidence to indicate the effect of an X trisomy on human fertility, as the strong relationship between an X trisomy and POI is clearly revealed [22]. In fact, our data may support that women with X chromosome mosaicism may experience premature menopause [13,20]. The prevalence of 47,XXX in cases with mosaic pattern was 10.7 %, which is higher than the prevalence reported by Goswami et al [5] (3.8%) and Jiao et al [12] (1.5%), respectively.…”
Section: Discussionmentioning
confidence: 54%
“…The different prevalence in these studies probably results from selection biases because women with primary amenorrhea were included for analysis in some of the studies from different countries. The strong relationship between X chromosome and ovarian function and the etiology of POI is commonly highlighted in the literature [5,13]. A Dutch study also indicated the relationship between X chromosome and the broader spectrum of menopausal age and POI [19].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although fluorescence in situ hybridization (FISH) may be the most appropriate method for detecting low level X chromosome mosaicism [9,14] we evaluated the presence of aneuploid metaphases by routine G-banding chromosome analysis, in order for the results to be comparable with some previous studies [5,6,12]. However, according to the International System for Human Cytogenetic Nomenclature (ISCN), numerical and structural abnormalities still have to be excluded at a banding level appropriate to the referral's guidelines [1,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider it to be the presence of ≤10 % of aneuploid cells [4][5][6], others the presence of <6 % of aneuploid cells [7]. It can be found in women with premature ovarian failure, infertility or a history of recurrent pregnancy loss [4][5][6][8][9][10][11][12][13][14]. In the general population X chromosome loss correlated with age has been described [1,3,15].…”
Section: Introductionmentioning
confidence: 99%